Symptomatic and functional recovery in depression in later life - Collard, Rose M. (Soc Psychiatry Psychiatr Epidemiol, 2018)
OBJECTIVES: Functional limitations give an indication of the total impact of diseases, such as depression, on individuals health and recovery. This study examines the change in several domains of functioning over 2 years in older persons depressed at baseline (non-remitted group and remitted group after 2 years) and in a non-depressed comparison group. METHODS: Data were used from a cohort study (Netherlands Study of Depression in Older persons [NESDO]) consisting of depressed older persons ≥ 60 years (N = 378) and a non-depressed comparison group (N = 132) with 2 years of follow-up (attrition rate 24%). Functional limitations (outcome) were assessed with the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) questionnaire every 6 months. Total scores and domain scores were used. Depression was classified according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) criteria at baseline and at 2-year follow-up. Severity of depression (predictor) was assessed with the Inventory of Depressive Symptomatology (IDS) at 6-month intervals. RESULTS: Linear mixed models showed that the level of functional limitations differed between the three groups during 2 years of follow-up. The non-remitted group had the highest level of functional limitations during 2 years, followed by the remitted group. Stable low levels of functional limitations were found for the non-depressed group. Remission from depression was accompanied by improvements in functioning, however, compared to the non-depressed comparison group significant functional limitations remained. Higher severity of depression appeared as risk factor for a declining course of functioning, especially the social aspects of functioning. METHODOLOGICAL CONSIDERATIONS: Participants that were more severely depressed and more functionally impaired at baseline had higher attrition rates than the participants that were included in the analytical sample. CONCLUSION: This study showed that depression in later life has long-term debilitating effects on functioning, enduring even after remission from depression. This implies that depression treatment in later life should aim broader than just symptomatic recovery, but also include functional recovery.